Marfan syndrome and twin pregnancy. Case report - García Pumasunta, Carolina (2019)
Marfan syndrome is a hereditary disorder of the connective tissue. Pregnant women who suffer from this syndrome have an increased risk of cardiac complications when the aortic diameter is greater than 40 mm. We present the case of a woman with twin pregnancy and preeclampsia and late diagnosis of Marfan syndrome. We discuss the need for early diagnosis, preconception counseling and multidisciplinary management in this type of pathology.